John Foster Dulles, illness, masculinity and U.S. foreign relations, 1953-1961 - Sewell, Bevan (Taylor & Francis, 2016)
In the last two decades, scholars have increasingly looked to understand the way that socially constructed norms and values have influenced the course of international diplomacy. Yet while much work has been produced on areas such as gender, far less has been written on the way that perceptions of illness affected the way that leading policymakers saw themselves, their allies, and their respective roles in the world. This article, by focusing on former US secretary of state John Foster Dulles, looks at the influence that perceptions of illness had on US foreign relations during the 1950s. First, it argues that US perceptions of British and French weakness – as typified by the ill-health being suffered by those nations’ respective leaders – shaped American responses to the diplomatic crisis that erupted over the battle of Dien Bien Phu in 1954. Second, it highlights the substantial changes that took place in US policy when first President Eisenhower, and then subsequently Secretary Dulles, were stricken down by severe illness. In doing so it demonstrates how a better understanding of the relationship between illness, emotions and masculinity can help historians to better understand the course of Cold War foreign relations.